RESPON PETANI TERHADAP SISTEM TANAM JAJAR LEGOWO DI KECAMATAN TUMIJAJAR KABUPATEN TULANG BAWANG BARAT - Erika Dwi Alviana; Dame Trully Gultom; Yuniar Aviati Syarief (Lampung University, 2018)
This study aims to examine the farmers' response to Legowo Row Planting System in Tumijajar Subdistrict of West Tulang Bawang Regency and factors related to farmers' responses to the Legowo Row Planting System. This research was conducted in Tumijajar subdistrict, West Tulang Bawang Regency. Data collection was conducted in May - August 2017. This research method used a survey method and using questionnaire as primary instrument of data collection. Data analysis used quantitative descriptive analysis to answer the first goal and Rank Spearman test to answer second goal. The results showed that farmers’ response to Legowo Row Planting System was relatively low. Factors related to farmer's response to Legowo Row Planting System are farmer’s age, formal education, length of farming experience, land size, motivation, and Sistem Tanam Jajar Legowo’s innovation characteristics. Key words: response, planting system, plant spacing